2010
DOI: 10.1124/jpet.110.171298
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Inhibitor Protects Cells against Light-Induced Retinal Degeneration

Abstract: Calpains are activated by excessive light exposure and related to retinal degeneration. We investigated the protective effects of ((1S)-1-((((1S)-1-benzyl-3-cyclopropylamino-2,3-di-oxopropyl)amino)carbonyl)-3-methylbutyl)carbamic acid 5-methoxy-3-oxapentyl ester (SNJ-1945), a calpain inhibitor, against lightinduced retinal degeneration in mice. SNJ-1945 was orally administrated at doses of 100 and 200 mg/kg at 30 min before and just after light exposure. Light-induced calpain activation was evaluated by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…ERG measurements in mice were performed as described in our previous report [50]. Electroretinograms (ERGs) were recorded 5 days after light exposure (Mayo, Aichi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…ERG measurements in mice were performed as described in our previous report [50]. Electroretinograms (ERGs) were recorded 5 days after light exposure (Mayo, Aichi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…19 ERG was recorded at 5 days after the ischemic surgery. Scotopic ERG was used to evaluate retinal function in the animals.…”
Section: Electroretinogram Recordingmentioning
confidence: 99%
“…Indeed, several studies have shown that exposure to high-intensity of light induces photoreceptor loss (light-damage model or LD) by several mechanisms that can be specific to the LD model 13 and by some other mechanisms that are common to other inherited retinal dystrophies. 14, 15 Interestingly, different studies showed that after LD the retina presents some cardinal features of AMD. 16, 17, 18, 19 For instance, LD leads to the accumulation of reactive oxygen species and generation of toxic metabolites such as N-retinylidene-N-retinylethanolamine (A2E), partially degraded proteins and lipid–protein adducts.…”
mentioning
confidence: 99%